2009
DOI: 10.1074/jbc.c900020200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of RNA Polymerase III Transcription Involves SCH9-dependent and SCH9-independent Branches of the Target of Rapamycin (TOR) Pathway

Abstract: Maf1 is a conserved repressor of transcription that functions at the downstream end of multiple nutrient and stress signaling pathways. How these different signaling pathways converge on Maf1 is not known. Previous work in yeast indicates that protein kinase A (PKA) regulates RNA polymerase (pol) III transcription, in part, by phosphorylating multiple sites in Maf1. Here we present additional evidence for this view and show that a parallel nutrient and stress-sensing pathway involving Sch9, an homologous kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(144 citation statements)
references
References 24 publications
2
141
1
Order By: Relevance
“…While this manuscript was in preparation, Lee et al (2009) reported that Sch9 phosphorylates Maf1; but, in contrast to our results, their work suggested that Sch9 and PKA perform equally important roles in Maf1 regulation. We believe that this discrepancy is due to protocol differences in the handling of yeast cells prior to protein extract.…”
Section: Maf1 Is a Direct Target Of Sch9contrasting
confidence: 99%
“…While this manuscript was in preparation, Lee et al (2009) reported that Sch9 phosphorylates Maf1; but, in contrast to our results, their work suggested that Sch9 and PKA perform equally important roles in Maf1 regulation. We believe that this discrepancy is due to protocol differences in the handling of yeast cells prior to protein extract.…”
Section: Maf1 Is a Direct Target Of Sch9contrasting
confidence: 99%
“…In yeast, Maf1 is regulated through phosphorylation by PKA and the TORC1-regulated Sch9 kinase (21,22). Phosphorylation of Maf1 at these sites results in its inactivation by preventing its nuclear accumulation under non-stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, both kinases have an additive effect for the expression of proteins required for nucleotide metabolism but they exert opposite effects on the expression on proteins involved in detoxification or proteolysis . In addition, they independently determine the sensitivity of yeast cells for the ATP-analogue 1NM-PP1 as illustrated by the observation that a mutant with combined analogue-sensitive sch9 as tpk1 as tpk2 as tpk3 as alleles is more sensitive than the single sch9 as mutant or the tpk1 as tpk2 as tpk3 as strain (Yorimitsu et al 2007;Huber et al 2009;Lee et al 2009). …”
Section: The Protein Kinase Sch9mentioning
confidence: 99%
“…For RNA polymerase III-dependent transcription, the downstream target of Sch9 is Maf1, the repressor that is also regulated by PKA and TORC1. Here, Sch9 was first reported to phosphorylate Maf1 at a subset of the sites that are also recognized by PKA (Lee et al 2009). Most recently, it was shown that Sch9 phosphorylates Maf1 at seven distinct sites in vitro and that it thereby can not only partially inhibit nuclear accumulation of Maf1 after rapamycin treatment, but also completely block the repressive association between Maf1 and the RNA Pol III subunit Rpc82 (Huber et al 2009).…”
Section: The Protein Kinase Sch9mentioning
confidence: 99%